2020
DOI: 10.1002/cncr.33152
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in mortality for patients with prostate cancer after radical prostatectomy

Abstract: Background Although racial disparities in prostate cancer survival are well documented, the relative importance of contributing factors remains unclear. Few studies have examined the disparity between Whites and Hispanics or between Whites and Asian Americans and Pacific Islanders (AAPIs). Methods Using data from the National Cancer Database for 526,690 patients with prostate cancer who underwent radical prostatectomy between 2004 and 2014, this study systematically evaluated the impact of clinical characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
1
22
1
Order By: Relevance
“…Our novel finding of a significantly higher case coverage rate for White versus Black Americans with genitourinary cancers is noteworthy in view of the well-described inferior treatment and survival outcomes among Black patients with these malignancies [ 6 , 12 , 13 , 14 , 15 ]. Interestingly, evidence demonstrating the presence and impact of racial disparities in prostate cancer and kidney cancer is particularly robust [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and it is these two malignancies which appear to be underlying the significantly higher overall genitourinary case capture rate in White versus Black subjects observed in the present analysis. Although disparities in urologic oncology are multifactorial and complex, differential access to cancer care undoubtedly plays a role in this phenomenon, and research derived from an equal-access healthcare system suggests that improved access to care may be key in mitigating racial disparities in genitourinary cancer outcomes [ 23 ].…”
Section: Discussionmentioning
confidence: 53%
“…Our novel finding of a significantly higher case coverage rate for White versus Black Americans with genitourinary cancers is noteworthy in view of the well-described inferior treatment and survival outcomes among Black patients with these malignancies [ 6 , 12 , 13 , 14 , 15 ]. Interestingly, evidence demonstrating the presence and impact of racial disparities in prostate cancer and kidney cancer is particularly robust [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and it is these two malignancies which appear to be underlying the significantly higher overall genitourinary case capture rate in White versus Black subjects observed in the present analysis. Although disparities in urologic oncology are multifactorial and complex, differential access to cancer care undoubtedly plays a role in this phenomenon, and research derived from an equal-access healthcare system suggests that improved access to care may be key in mitigating racial disparities in genitourinary cancer outcomes [ 23 ].…”
Section: Discussionmentioning
confidence: 53%
“…Recently, Wen et al [ 43 ] evaluated the impact of clinical characteristics and factors related to access to care on survival by race using data from the NCDB for 526,690 patients with prostate cancer who underwent radical prostatectomy. In their study, when adjustments were made for age and year of diagnosis only, it was observed that the Black, AAPIs (Asian Americans and Pacific Islanders), and Hispanic population had 51% higher mortality, 22% lower mortality, and 6% lower mortality, respectively compared to the Caucasian population.…”
Section: Racial Difference and Treatmentmentioning
confidence: 99%
“…Studying men presenting at a large number of US hospitals in the US National Cancer Database, Wen et al 3 assessed the effectiveness of prostate cancer treatment, primarily radical prostatectomy, in the United States. They found that Black men with high‐grade, localized disease treated with radical prostatectomy had a 51% higher mortality rate (hazard ratio [HR], 1.51; 95% confidence interval, 1.47‐1.56).…”
mentioning
confidence: 99%
“…Wen et al's study 3 is one of the few that have assessed outcomes among Asian American/Pacific Islander (AAPI) and Hispanic patients. It leaves us asking why AAPI and Hispanic patients as a group have better outcomes than Whites.…”
mentioning
confidence: 99%